Dietary flavonoid intake and the risk of stroke: a dose-response meta-analysis of prospective cohort studies - Tang, Zhenyu (BMJ Open, 2016)
OBJECTIVE: To clarify and quantify the potential association between intake of flavonoids and risk of stroke. DESIGN: Meta-analysis of prospective cohort studies. DATA SOURCE: Studies published before January 2016 identified through electronic searches using PubMed, Embase and the Cochrane Library. ELIGIBILITY CRITERIA FOR SELECTING STUDIES: Prospective cohort studies with relative risks and 95% CIs for stroke according to intake of flavonoids (assessed as dietary intake). RESULTS: The meta-analysis yielded 11 prospective cohort studies involving 356 627 participants and more than 5154 stroke cases. The pooled estimate of the multivariate relative risk of stroke for the highest compared with the lowest dietary flavonoid intake was 0.89 (95% CI 0.82 to 0.97; p=0.006). Dose-response analysis indicated that the summary relative risk of stroke for an increase of 100 mg flavonoids consumed per day was 0.91 (95% CI 0.77 to 1.08) without heterogeneity among studies (I(2)=0%). Stratifying by follow-up duration, the relative risk of stroke for flavonoid intake was 0.89 (95% CI 0.81 to 0.99) in studies with more than 10 years of follow-up. CONCLUSIONS: Results from this meta-analysis suggest that higher dietary flavonoid intake may moderately lower the risk of stroke.